1988
DOI: 10.1002/jez.1402480208
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine metabolism by the perfused rainbow trout gill

Abstract: The trout gill has the capacity to influence general adrenergic activity through extraction and metabolism of circulating catecholamines (CAI; (Nekvasil and Olson, Am. J. Physiol., 1986,250:R526-R531). To further examine the metabolic process, isolated gills were perfused with M and lo-" M norepinephrine (NEPI) or epinephrine (EPI) and effluent from the arterioarterial (AA) and arteriovenous (AV) pathways analyzed by high pressure liquid chromatography with electrochemical detection (HPLC-EC). After 20 minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It is evident from the studies compiled in the aforementioned review that there are marked differences in the levels of plasma catecholamines observed in different species in response to different types of stress. The dominance of either adrenaline or noradrenaline in the circulation during a stressful period is not only dependent upon storage levels [25,28,41,42,66,220] but also on the rate of metabolic degradation [56,191,192], accumulation of catecholamines into tissues [40,190,191,271,272] and the 'ability' of chromaffin cells to secrete catecholamines [239].…”
Section: Situations Eliciting Catecholamine Secretionmentioning
confidence: 99%
“…It is evident from the studies compiled in the aforementioned review that there are marked differences in the levels of plasma catecholamines observed in different species in response to different types of stress. The dominance of either adrenaline or noradrenaline in the circulation during a stressful period is not only dependent upon storage levels [25,28,41,42,66,220] but also on the rate of metabolic degradation [56,191,192], accumulation of catecholamines into tissues [40,190,191,271,272] and the 'ability' of chromaffin cells to secrete catecholamines [239].…”
Section: Situations Eliciting Catecholamine Secretionmentioning
confidence: 99%
“…The anatomical similarities of the mammalian pulmonary vasculature and the gill, i.e., both receive the entire cardiac output and have extensive endothelial (or pillar) cell surface area, has prompted an investigation into the ability of gill vessels to also "condition" plasma prior to systemic perfusion. Recent studies have indicated that the gill vasculature has attributes similar to the lung; i.e., it activates angiotensin I1 and extracts andlor metabolizes adenosine, catecholamines, serotonin, and bradykinin, and products of the arachidonic acid cascade (Colin and Leray, 1979;Colletti and Olson, 1988;Galardy et al, 1984;Hemker, 1987;Kullman and Olson, 1989;Lipke and Olson, 1988;Nekvasil and Olson, 1986;Olson et al, 198613;. However, unlike the pulmonary circulation, which is a single pass perfusion, blood perfusing the gill may pass through one (arterioarterial) or two (arterioarterial plus arteriovenous) microvascular networks.…”
Section: Fig 4 Diagrammatic Cross Section Through Filament and Lamementioning
confidence: 99%